KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR PADA MODEL JIGSAW BERBANTU MEDIA PERMAINAN TRADISIONAL ENGKLEK - Fadliansyah, Fauzi (LPPM Universitas Bina Bangsa, 2025)
This study aims to determine how to improve students' mathematical communication skills in the Jigsaw model assisted by the traditional Engklek game. This study uses a quantitative research type. The sample population was conducted at SDN Cibeber, Cilegon City with a sample of class V. This study uses Side Random. The instrument used was a test question with a total of 5 questions about mathematical communication questions. Data analysis used Validity Test, Prerequisite Test and Hypothesis Analysis Test. The results of the study showed that there was a difference between the control and experimental classes in the research process, namely the experimental class was superior to the control class because it used the Jigsaw model assisted by the Traditional Engklek game media